2004
DOI: 10.2166/wst.2004.0737
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from sludge reject water by a two-stage oxygen-limited autotrophic nitrification denitrification process

Abstract: Nitrogen removal from sludge reject water was obtained by oxygen-limited partial nitritation resulting in nitrite accumulation in a first stage, followed by autotrophic denitrification of nitrite with ammonium as electron donor (similar to anaerobic ammonium oxidation) in a second stage. Two membrane-assisted bioreactors (MBRs) were used in series to operate with high sludge ages and subsequent high volumetric loading rates, achieving 1.45 kg N m(-3) day(-1) for the partial nitritation MBR and 1.1 kg N m(-3) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 12 publications
3
34
0
4
Order By: Relevance
“…The process eliminates the requirements of aeration and exogenous organic carbon sources compared to the traditional nitrification-denitrification process of nitrogen removal. However, slow growth rate of the anammox bacteria and toxicity issues forced the early development of the process with biofilms, granulation, and suspended biomass reactors [9][10][11]. The process requires the combination of two processes, nitritation and anammox reaction, which, in engineered systems, can either be separated in time or space.…”
Section: Anammox Processmentioning
confidence: 99%
“…The process eliminates the requirements of aeration and exogenous organic carbon sources compared to the traditional nitrification-denitrification process of nitrogen removal. However, slow growth rate of the anammox bacteria and toxicity issues forced the early development of the process with biofilms, granulation, and suspended biomass reactors [9][10][11]. The process requires the combination of two processes, nitritation and anammox reaction, which, in engineered systems, can either be separated in time or space.…”
Section: Anammox Processmentioning
confidence: 99%
“…Studies have shown that the composition and diversity of microbial communities is important in nitrogen transformation and removal processes [9], [10]. The process of nitrificationdenitrification is a microbial process which comprises of two phases [11]. The first, known as nitrification, is an aerobic process carried out by Gram-negative, in which ammonium is oxidized to nitrite (NO 2 − ) by means of ammonia oxidizing bacteria (AOB).…”
Section: Introductionmentioning
confidence: 99%
“…Se han definido diferentes concentraciones de OD para llevar a cabo la nitrificación parcial, que van desde 0.3 a 2.5 mg/l (Wyffels et al 2004a(Wyffels et al , 2004b. Altas concentraciones de OD (> 2 mg/l) podrían convertir la nitrificación parcial en completa, mientras que concentraciones inferiores a 0.5 mg/l puede reducir considerablemente la tasa de nitrificación.…”
Section: Proceso De Nitrificación Parcial -Desnitrificación (Proceso unclassified